2015
DOI: 10.1016/j.snb.2014.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of electrochemically active biofilm developing behavior on bioanode by using EQCM and ATR/FTIR

Abstract: It is crucial to study the bacterial attaching behavior for revealing information of electrochemically active biofilm on the interface of liquid/electrode in microbial fuel cells (MFCs). In the current study, mixed-culture from waste water as model bacteria was investigated for gaining more sight onto relationship between current and biomass or onto bioadhesion mechanism at the molecular level using Electrochemical Quartz Crystal Microbalance (EQCM) and Attenuated Total Reflection-SEIRAS (ATR-SEIRAS) combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Moreover, atomic force microscopy (AFM) analysis of the used gold disks showed that the αAgNAs treatment removed the matrix material (Figure B), which otherwise embeds the cells on the untreated gold disk (Figure A). Taking into account the hydrolytic activity of αAgNAs (Figure ) and the reported water displacement during EPS production, the observed frequency and dissipation shifts, after the addition of αAgNAs, were attributed to an increase of the biofilm water content due to the degradation of the EPS. In fact, water exchange has been reported to compensate mass changes on the disk surface with the adherence of cells. , Furthermore, the loss of water has been associated with an increase in the strength of the cell-surface contact .…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, atomic force microscopy (AFM) analysis of the used gold disks showed that the αAgNAs treatment removed the matrix material (Figure B), which otherwise embeds the cells on the untreated gold disk (Figure A). Taking into account the hydrolytic activity of αAgNAs (Figure ) and the reported water displacement during EPS production, the observed frequency and dissipation shifts, after the addition of αAgNAs, were attributed to an increase of the biofilm water content due to the degradation of the EPS. In fact, water exchange has been reported to compensate mass changes on the disk surface with the adherence of cells. , Furthermore, the loss of water has been associated with an increase in the strength of the cell-surface contact .…”
Section: Resultsmentioning
confidence: 94%
“…These two reactions compete in the course of the electrochemical CO 2 reduction. Surface-enhanced infrared adsorption spectroscopy (SEIRAS) has been employed to investigate the mechanism of the CO 2 reduction reaction. , Wuttig et al revealed that bicarbonate served as a proton donor following the rate-limiting step . Dunwell et al also studied the function of bicarbonate in the electrochemical reduction of CO 2 on an Au surface using the SEIRAS technique and proposed that CO 2 reduction benefitted from the rapid equilibrium of bicarbonate species and dissolved CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu's group studied the in situ interactions between the bacteria and the solid electrode during the biofilm formation at the status from early to over‐growth mature by Electrochemical Quartz Crystal Microbalance (EQCM) and EC‐SEIRAS [55]. They investigated the relationship between biomass and current according to the bio‐electrogenic process of the Geobacter sulfurreducens biofilm and found that the cellular biomass on the surface of the QCM‐crystal showed a maximum value from 6.0 to 11.5 μg/cm 2 on the biofilm from early formation status to mature status accompanied by a similar maximum current density ( ca .…”
Section: Surface‐enhanced Infrared Absorption Spectroscopy (Seiras)mentioning
confidence: 99%